Epidemiology and Presentation of Malaria among Population of Karachi, Pakistan - Memon, Arslan; Syed, Muhammad Asif; Tahir, Shumaila; Tahir, Syeda Anjala; Huma, Zille (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Malaria is widespread in Pakistan. It is a major threat to public health. Malaria presents in various forms, and its clinical presentation varies in different age groups and comorbid conditions. It is important to understand the recent epidemiology and presentation of malaria in our part of the world so that we can treat it effectively and further decrease mortality from this treatable and preventable disease. Aim: To determine the epidemiology and presentation of malaria in Karachi. Methods: This study was conducted at the Malaria Control Program clinic at Ruth K.M. Pfao Civil Hospital, Karachi, from January 2020 to December 2020. Patients of either gender and of any age with suspected symptoms of malaria were included in the study. Samples were collected to identify parasites. Patients were asked about clinical features and noted in proforma. Statistical analysis was performed using SPSS-20. Results: A total of 197 patients were included in this study, out of which 114 were males and 83 were females. 172 belonged to the province of Sindh, while the remaining belonged to Baluchistan province. Plasmodium falciparum was found in 22 [11.2%] patient samples, while vivax was present in a majority of 175 [88.8%] patients. The highest numbers of patients were reported in the winter months, from January to March. Fever was the most common complaint, at almost 95.4%. Chills, weakness, and body aches were also present in 25.9%, 21.3%, and 18.3%. Practical Implication: The study emphasizes the significance of focusing intervention programs on geographical variations in malaria prevalence, taking into account the demographic features of patients. Given that Plasmodium vivax is the most common species, it highlights the necessity of species-specific treatment approaches. Conclusion: Malaria is most commonly found during the winter months. The most common clinical features are fever, chills, weakness, and body aches.